A Novel Dye-Doped Sol–Gel Silica Sorbent for the Removal of Cobalt - Aslam Khan; Shujaat Ahmed; Farzana Mahmood; M. Younas Khokhar (Adsorption Science & Technology)
A TAR [4-(2-thiazolylazo)resorcinol] doped sol–gel silica sorbent (red colour, porous, stable, hard, non-swelling) was prepared, characterized and investigated for the removal of Co(II) from aqueous solutions. The kinetics, adsorption isotherm, equilibration time and effect of pH on such removal were studied to optimize the conditions necessary for large-scale application. Rapid equilibration was observed with adsorption equilibria being attained within 10 min. The adsorption of cobalt ions onto the plain (undoped) sol–gel silica was negligible. The maximum adsorption of Co(II) ions onto the TAR-doped sol–gel silica from single solutions was 12.6 mmol/g. The TAR-doped sol–gel silica could be regenerated by washing with a 0.1 M HCl solution to give a maximum regeneration value as high as 98.5%. The TAR-doped sol–gel silica could be used for more than three consecutive adsorption/desorption cycles without experiencing any considerable loss of adsorption capacity. The adsorption process and the nature of the Co–TAR complex were discussed.